Immune mediators as predictive biomarkers for anti-PD-1 antibody therapy in urothelial carcinoma - Shibata, Yosuke; Kishida, Takeshi; Kouro, Taku; Wei, Feifei; Igarashi, Yuka; Himuro, Hidetomo; Noguchi, Takeaki; Koizumi, Mitsuyuki; Suzuki, Takahisa; Osaka, Kimito; Saigusa, Yusuke; Sasada, Tetsuro (Frontiers in Pharmacology, 2023)
Background and objectives: To Introduction: This study aimed to identify immune mediators, including cytokines, chemokines, and growth factors, in the plasma for predicting treatment efficacy and immune-related adverse events (irAEs) in advanced urothelial carcinoma (aUC) treated with immune checkpoint inhibitors (ICIs). Methods: Methods: We enrolled 57 patients with aUC who were treated with the anti-programmed cell death protein 1 (PD-1) antibody pembrolizumab after the failure of platinum-based chemotherapy between February 2018 and December 2020. Plasma levels of 73 soluble immune mediators were measured before and six weeks after initiating pembrolizumab therapy. The association of estimated soluble immune mediators with clinical outcomes, including overall survival (OS), progression-free survival (PFS), anti-tumour tumor responses, and irAEs, were statistically evaluated. Results: Results: In the multivariate analysis, levels of 18 factors at baseline and 12 factors during treatment were significantly associated with OS. Regarding PFS, baseline levels of 17 factors were significantly associated with PFS. Higher levels of interleukin (IL)-6, IL-8, soluble tumour tumor necrosis factor receptor 1 (sTNF-R1), and IL-12 (p40), both at baseline and post-treatment, were significantly associated with worse OS. Conversely, low IL-6 and high TWEAK levels at baseline were associated with irAEs. Among identified factors, interferon (IFN) γ and IL-12 (p40) were repeatedly identified; high baseline levels of these factors were risk factors for worse OS and PFS, as well as progressive disease. Notably, using correlation and principal component analysis, factors significantly associated with clinical outcomes were broadly classified into three groups exhibiting similar expression patterns. Conclusion: Discussion: Measuring plasma